2022
DOI: 10.1002/acm2.13579
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning‐based auto segmentation using generative adversarial network on magnetic resonance images obtained for head and neck cancer patients

Abstract: Purpose Adaptive radiotherapy requires auto‐segmentation in patients with head and neck (HN) cancer. In the current study, we propose an auto‐segmentation model using a generative adversarial network (GAN) on magnetic resonance (MR) images of HN cancer for MR‐guided radiotherapy (MRgRT). Material and methods In the current study, we used a dataset from the American Association of Physicists in Medicine MRI Auto‐Contouring (RT‐MAC) Grand Challenge 2019. Specifically, eight structures in the MR images of HN regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Cross-sectional CT and MRI are an integral part of the diagnostic workup. Applications of novel narrow-specific AI tasks in these imaging techniques have shown promise for data acquisition, image segmentation and registration, and assessment of tumor responses to therapy in brain tumors [30], breast [32], head and neck [33,35], liver, lung, and abdominal cancers [29,61,127]. For example, the DL method has exhibited as an effective and clinically applicable tool for the segmentation of the head and neck anatomy for radiotherapy [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-sectional CT and MRI are an integral part of the diagnostic workup. Applications of novel narrow-specific AI tasks in these imaging techniques have shown promise for data acquisition, image segmentation and registration, and assessment of tumor responses to therapy in brain tumors [30], breast [32], head and neck [33,35], liver, lung, and abdominal cancers [29,61,127]. For example, the DL method has exhibited as an effective and clinically applicable tool for the segmentation of the head and neck anatomy for radiotherapy [34].…”
Section: Discussionmentioning
confidence: 99%
“…AI efforts in CT and MRI are already well underway and have demonstrated remarkable progress in various image analysis tasks [8][9][10][11]. In cancer screening, DL techniques have shown promise in CT screening for lung cancer and colonic polyps [28], MRI screening for prostate cancer [29], discriminating glioblastoma from brain metastasis with conventional MR images [30], breast cancer risk assessment with MR images [31,32], and segmentation of CT and MR images of head and neck (HN) cancer for MR-guided radiotherapy [33][34][35]. AI models trained on large datasets can extract high-dimensional representations, which show an increase in specificity compared with lower-dimensional machine learning methods often used in computer-aided detection software for lung cancer screening [36].…”
Section: Ai In Ct and Mri For Oncological Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…With the introduction of deep learning (DL) technology in radiotherapy, the performance of autosegmentation algorithms has improved substantially. [4][5][6][7][8][9] A substantial number of papers, of which we will only cite the reviews [10][11][12] and some recent efforts, [13][14][15][16][17] were devoted specifically to autosegmentation of HN organs at risk (OARs).As a logical first step, quality of OAR autosegmentation is often judged by geometric concordance metrics against the human-generated reference structures, [18][19][20][21][22] sometimes followed by a forward dosimetric analysis, for example, comparing the dose-volume histograms (DVHs) for the machine-generated structures against the manual ones, based on the original dose distribution. However, the real goal of autosegmentation is the inverse ability: the quality of a plan generated on the (unedited) autosegmented structures should be maintained if the manual OARs are substituted for the automatic ones during the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…While it was suggested that accurate delineation of salivary and swallowing structures may not be necessary for satisfactory Head and Neck (HN) treatment planning, 3 the prevailing effort is clearly focused on improving the contours’ quality. With the introduction of deep learning (DL) technology in radiotherapy, the performance of autosegmentation algorithms has improved substantially 4–9 . A substantial number of papers, of which we will only cite the reviews 10–12 and some recent efforts, 13–17 were devoted specifically to autosegmentation of HN organs at risk (OARs).…”
Section: Introductionmentioning
confidence: 99%